2021
DOI: 10.1177/00405175211055070
|View full text |Cite
|
Sign up to set email alerts
|

A study of the physical properties and bending stiffness of antistatic and antibacterial knitted fabrics

Abstract: Different fiber blends, knit patterns, and treatments may be applied to increase the functionality and comfort of knitted fabrics. In this research, the physical properties and bending stiffness of 1 × 1 rib and half-milano rib fabrics with four fiber blends (90% cotton/10% antistatic PET, 80% cotton/20% antistatic PET, 70% cotton/30% antistatic PET, and 65% cotton/35% antistatic PET) applied to each knit pattern were studied. The effect of fabric direction (course and wale), technical side (face side and back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…It is also observed from Figure 3 that seams need less force to bend in the course direction than in the wales direction. This is similar to the results given by Asfand and Daukantien_ e, 14 where the bending stiffness is lower in the course direction than in the wales direction. recovery average rigidity, which are given in Figures 4 and 5 respectively.…”
Section: Influence Of Stitch Density On Seam Bending Behavioursupporting
confidence: 92%
“…It is also observed from Figure 3 that seams need less force to bend in the course direction than in the wales direction. This is similar to the results given by Asfand and Daukantien_ e, 14 where the bending stiffness is lower in the course direction than in the wales direction. recovery average rigidity, which are given in Figures 4 and 5 respectively.…”
Section: Influence Of Stitch Density On Seam Bending Behavioursupporting
confidence: 92%
“…For example, Choi and Ashdown and Ashdown 27 noted that by increasing the 1 × 1 rib cotton fabric weight and stitch density (from 590 to 660 g/m 2 and 23.35 to 35.32 cm 2 , respectively), fabric stiffness increased about two times. Asfand and Daukantienė 28 reported a linear relationship between 1 × 1 rib cotton/PET fabrics’ bending stiffness and two fabric structural parameters: weight and density.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is known from practice that fashion designers make their decisions based on fabric aesthetics appearance, and only then analyze its performance. However, previous research revealed 36 that even knitted fabrics look very similar for 1×1 rib and half-Milano rib patterns for both technical sides, they demonstrate different bending behavior depending not only on the knit pattern, but also on their technical side. Therefore, the aim was to investigate the influence of the fabric knit pattern, technical side, percentage of fiber mixture, and treatment on the moisture management and air permeability properties of newly developed cotton/antistatic polyester knitted fabrics, suggesting the use of them for regular application in clothing manufacturing.…”
Section: Introductionmentioning
confidence: 86%